Honey bee maternal effects improve worker performance and reproductive ability in offspring - Yu, Longtao; He, Xujiang; Shi, Xinxin; Yan, Weiyu; Wu, Xiaobo (Frontiers in Cell and Developmental Biology, 2023)
Maternal effects are an evolutionary strategy used to improve offspring quality. In an example of maternal effects in honey bees (Apis mellifera), mother queens produce larger eggs in queen cells than in worker cells in order to breed better daughter queens. In our current study, physiological indexes, reproductive tissues, and the egg-laying ability of newly reared queens reared with eggs laid in queen cells (QE), eggs laid in worker cells (WE), and 2-day-old larvae in worker cells (2L) were evaluated. In addition, morphological indexes of offspring queens and working performance of offspring workers were examined. The thorax weight, number of ovarioles, egg length, and number of laid eggs and capped broods of QE were significantly higher than those of WE and 2L, indicating that the reproductive capacity of QE group was better than that of other groups. Furthermore, offspring queens from QE had larger thorax weights and sizes than those from the other two groups. Offspring worker bees from QE also had larger body sizes and greater pollen-collecting and royal jelly-producing abilities than those of other two groups. These results demonstrate that honey bees display profound maternal effects on queen quality that can be transmitted across generations. These findings provide a basis for improving queen quality, with implications in apicultural and agricultural production.